Characterisation of SalRAB a salicylic acid Inducible positively regulated efflux system of Rhizobium leguminosarum bv viciae 3841 - Tett, A; Karunakaran, R; Poole, P (Public Library of Science, 2014)
Salicylic acid is an important signalling molecule in plant-microbe defence and symbiosis. We analysed the transcriptional responses of the nitrogen fixing plant symbiont, Rhizobium leguminosarum bv viciae 3841 to salicylic acid. Two MFS-type multicomponent efflux systems were induced in response to salicylic acid, rmrAB and the hitherto undescribed system salRAB. Based on sequence similarity salA and salB encode a membrane fusion and inner membrane protein respectively. salAB are positively regulated by the LysR regulator SalR. Disruption of salA significantly increased the sensitivity of the mutant to salicylic acid, while disruption of rmrA did not. A salA/rmrA double mutation did not have increased sensitivity relative to the salA mutant. Pea plants nodulated by salA or rmrA strains did not have altered nodule number or nitrogen fixation rates, consistent with weak expression of salA in the rhizosphere and in nodule bacteria. However, BLAST analysis revealed seventeen putative efflux systems in Rlv3841 and several of these were highly differentially expressed during rhizosphere colonisation, host infection and bacteroid differentiation. This suggests they have an integral role in symbiosis with host plants.